How are Portuguese venture capitalists weighting the skills of the entrepreneur when evaluating a venture opportunity? - Guimarães, Ana Rita Pais (2016)
Startups can raise money from several sources but one of the most common is through Venture Capital. There is an interest in better understanding how venture capital deals come together, as entrepreneurs know too well how difficult it can be to raise funds. Hence, the objective of this thesis is to analyze if the entrepreneur, its competencies and skills, do play a major role in the venture capitalists’ seed-stage investment decision process with a focus on Portugal. The collection of primary data, through surveys and interviews, pinpointed the entrepreneur as one of the most important factors that ultimately influences the funding decision. Additionally, a cohesive start-up team, founders presenting relevant previous experience (startup and managerial), as well as technical and market expertise, and face-to-face interactions (between entrepreneurs and Venture Capitalists), in which storytelling ability plays a role, also favorably increase the odds of successful funding. On the other hand, two factors that were not conclusively validated with this current analysis were i) direct and/or indirect ties between entrepreneurs and Venture Capitalists and ii) entrepreneur’s social skills. These were not considered direct fundraising drivers and will require further investigation.